Neuroprotective potential of secondary metabolites from Melicope lunu-ankenda (Rutaceae) - Mohamed, Zeinab Abdulwanis; Eliaser, Enas Mohamed; Mazzon, Emanuela; Rollin, Patrick; Ee, Gwendoline Cheng Lian; Abdull Razis, Ahmad Faizal (MDPI, 2019)
Plant natural compounds have great potential as alternative medicines for preventing and treating diseases. Melicope lunu-ankenda is one Melicope species (family Rutaceae), which is widely used in traditional medicine, consumed as a salad and a food seasoning. Consumption of different parts of this plant has been reported to exert different biological activities such as antioxidant and anti-inflammatory qualities, resulting in a protective effect against several health disorders including neurodegenerative diseases. Various secondary metabolites such as phenolic acid derivatives, flavonoids, coumarins and alkaloids, isolated from the M. lunu-ankenda plant, were demonstrated to have neuroprotective activities and also exert many other beneficial biological effects. A number of studies have revealed different neuroprotective mechanisms for these secondary metabolites. This review summarizes the most significant and recent studies for neuroprotective activity of M. lunu-ankenda major secondary metabolites in neurodegenerative diseases.